JEJAK INTELEKTUAL MUSLIM KLASIK: FONDASI ILMU SOSIAL DAN METODOLOGI PENELITIAN DALAM SOSIOLOGI, SEJARAH, DAN PSIKOLOGI - Lestari, Liza Puji; Ismail, Fajri; Zuhdiyah, Zuhdiyah; Ismail, Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The thoughts of classical Muslim intellectuals such as Ibn Khaldun, Al-Thabari, and Al-Ghazali are very important for the development of social sciences and research methods. Ibn Khaldun is known for his ideas about society and systematic methods in sociology. Al-Thabari wrote history in a neat way and used original sources carefully. While Al-Ghazali combined thoughts about the soul, reason, and spirituality to understand human psychology. These three figures help us understand social sciences in a complete and balanced way, and their thoughts are still very useful for social sciences today, especially in the context of Islamic culture and religion. The method in this study is qualitative. The results of this study are that the thoughts of Ibn Khaldun, Al-Thabari, and Al-Ghazali made a major contribution to the foundation of social sciences and research methodology among classical Muslim intellectuals with complementary approaches; Ibn Khaldun laid the foundation of sociology with a critical analysis of social dynamics and societal change, Al-Tabari developed a systematic and narrative historical methodology with in-depth verification of sources and socio-cultural contexts, while Al-Ghazali integrated spiritual and rational aspects into Islamic psychology with an emphasis on the balance between reason and heart and moral and spiritual development to achieve holistic mental health.